IN SEARCH OF THE OPTIMAL CUFF FOR BLOOD PRESSURE MEASUREMENT IN THE VERY OBESE. (April 2021) - Palatini, Paolo; Benetti, Elisabetta; Fania, Claudio; Ermolao, Andrea; Spinella, Paolo; Battista, Francesca; Gasperetti, Andrea; Saladini, Francesca
Abstract : Objective: Rectangular (cylindrical) cuffs and bladders are currently used for blood pressure (BP) measurement at the upper arm. However, large arms have a conical shape which make cylindrical cuffs potentially unsuitable. Aim of this study was to study the shape of the arm in people with severe obesity and to investigate the effect of the shape of the cuff on BP measurement in these subjects. Design and method: In 79 obese subjects with upper arm mid-circumference >40 cm and 79 subjects of control, cylindrical and tronco-conical cuffs of appropriate size were compared. We considered the upper arm either as a single truncated cone (model 1) or as the sum of two tronco-conical shapes, with bases at the proximal and middle arm circumference, respectively (model 2). The frustum slant angle of the proximal (upper angle) and distal (middle angle) truncated cones were measured. If the difference between upper and middle angles is equal to zero, the upper arm can be assimilated to a single truncated cone as in model 1. If the difference is positive (model 2), it means that the distal half of the arm is more conical than the proximal half. Results: In the Obese, upper angle was greater than middle angle, whereas in the Nonobese the two angles were similar (p < 0.0001 versus Obese for both angles). In the Obese, the cylindrical cuff overestimated BP measured with the tronco-conical cuff by 4.3 ± 5.4/3.1 ± 4.7 mmHg, whereas in the Nonobese slight discrepancies were found between the two cuffs (p < 0.0001/<0.0001versus Obese). In the whole study sample, the difference between the upper and middle angles was correlated with systolic BP (p = 0.0008) and diastolic (p < 0.0001) BP discrepancies. In a multivariable linear regression, the difference between the two angles was an independent predictor of the between-cuff BP differences in obese men (p = 0.004/0.0007) but not in obese women. Conclusions: In very obese people, the tronco-conical shape of the upper-arm is more pronounced on the distal than the proximal half, a feature that amplifies the BP measurement error when cylindrical cuffs are used.